Influent fractionation for the use of ASM1 to optimize urban wastewater treatment: Application to the removal of C and N in a SBR - Casellas, Magali; Dagot, Christophe; Pons, Marie-Noëlle; Baudu, Michel (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2008)
AbstractA simulation of a SBR using Benchmark procedure was done prior to field operation in order to optimize the cycle and phases lengths. The accurate identification of ASM1 variables is a prerequisite to achieve a good prediction. A fractionation procedure was applied to samples, corresponding to dry and rainy weather conditions, for taking into account the ASM1 state variable characteristics of specific wastewater (mixture of domestic and industrial wastewater), which differ largely from the default ones used in ASM1. The choice of the ASM1 state variables identification methodology is very important as it influences the results. Two methods were carried out: a batch test in closed reactors, and a coagulation/flocculation procedure. An optimal 12‑hour cycle length was determined, in terms of discharged water quality and reactor productivity. The described methodology led to valuable results in terms of carbon and nitrogen removal: respectively more than 90% of COD removal and more than 80% on total nitrogen removal.